Construction of the ultrasonic pulse radar on the LabVIEW and Elvis platform - Yeo, Michelle (2014)
The purpose of the project on the Construction of the Ultrasonic Pulse Radar is to build a project demonstration to illustrate the concept of radar principles for the benefit of future students who will be studying and learning to use National Instruments LabVIEW and the Elvis platform as a part of the study curriculum.